New species of Campylaimus (Diplopeltidae, Nematoda) from Argentinean coasts (Buenos Aires and Santa Cruz, Argentina) - Villares, Maria Gabriela (2013)
Two new Campylaimus species from Arroyo Pareja, Buenos Aires province and one new species and one new record of Campylaimus from Puerto San Julián, Chubut province are described. The three species are characterized by the shape of the copulatory apparatus of the male and the presence of precloacal papillae. Campylaimus bonariensis sp. nov. has slen-der and arcuate spicules, with well-developed cephalization at the proximal end, tubular gubernaculum and three preclo-acal papillae; Campylaimus arcuatus sp. nov. has curved spicules, with well-developed cephalization at the proximal end, gubernaculum with dorso-caudally directed apophysis and five precloacal papillae; Campylaimus patagonicus sp. nov. has slender and arcuate spicules without proximal cephalization, gubernaculum with dorso-caudally directed apophysis and two precloacal papillae. An emended diagnosis of the genus Campylaimus and an identification key to species based on male characters are given the tail-color discrepancy. Only McAtee (1942) concluded that his description could be fully accurate as written, indicating a bird closely related to, but different from, a typical King Vulture. Paralleling Bartram’s description is an apparently independent account and painting of a vulture of uncertain geo-graphic origin by Eleazar Albin (1734). Details of Albin’s description, including tail color, are very similar to those of Bartram’s description. The only discrepancies are minor differences in color of softparts and tail that seem explicable as intraspecific variation. Available evidence suggests that Bartram knew nothing of Albin’s description, and if so, Albin’s bird provides quite persuasive support for the validity of Bartram’s bird. Equally important, none of the arguments offered historically against the validity of the Painted Vulture is persuasive when examined closely. Together, these and other fac-tors make a strong case for acceptance of Bartram’s Painted Vulture as a historic resident of northern Florida and likely other adjacent regions.